Arterial Spin Labeling Imaging Assessment of Cerebrovascular Reactivity in Hypertensive Small Vessel Disease - Lee, Bo-Ching; Tsai, Hsin-Hsi; Huang, Abel Po-Hao; Lo, Yen-Ling; Tsai, Li-Kai; Chen, Ya-Fang; Wu, Wen-Chau (Frontiers in Neurology, 2021)
Objective: Cerebrovascular reactivity (CVR) represents the phenomenon where cerebral vessels dilate or constrict in response to vasoactive stimuli. CVR impairment may contribute to the brain injury due to cerebral small vessel disease (SVD). We aimed to determine the CVR in hypertensive intracerebral hemorrhage (ICH) and to identify its vascular dysfunction. Methods: A total of 21 patients with spontaneous hypertensive ICH (strictly deep or mixed deep and lobar hemorrhages, mean age 62.5 ± 11.3 years) and 10 control subjects (mean age 66.1 ± 6.0 years) were enrolled for CVR measurement at least 3 months after the symptomatic ICH event. Each participant underwent a brain MRI study, and CVR was calculated as the cerebral blood flow (CBF) reduction using arterial spin labeling (ASL) between baseline and 10 minutes after an intravenous dipyridamole injection (0.57 mg/kg). Traditional MRI markers for SVD were also evaluated, including cerebral microbleed, white matter hyperintensity, lacune, and MRI-visible enlarged perivascular space, which were used to determine the total small vessel disease score. Results: Compared to control subjects, hypertensive ICH patients showed reduced CVR in the basal ganglia (CBF reduction 22.4 ± 22.7% vs. 41.7 ± 18.3, p=0.026), the frontal lobe (15.1 ± 11.9 vs. 26.6 ± 9.9, p=0.013), and the temporal lobe (14.7 ± 11.1 vs. 26.2 ± 10.0, p=0.010). These differences remained significant in multivariable models after adjusting for age and sex. Within ICH groups, the CBF reduction in the basal ganglia was significantly correlated with the total small vessel disease score (R=0.58, p=0.006), but not with individual MRI markers. Conclusion: Patients with advanced hypertensive SVD demonstrated impaired vasoconstriction after dipyridamole challenge in the basal ganglia and the frontal and temporal lobes. Our findings provide safe approaches for whole-brain CVR mapping in SVD and identify a potential physiological basis for vascular dysfunction in hypertensive SVD.